Effect of Blade Outlet Angle on Radial Force of Marine Magnetic Drive Pump - Hong-li Zhang; Fan-yu Kong; Ai-xia Zhu; Fei Zhao; Zhen-fa Xu (Shock and Vibration)
To research the effects of the blade outlet angle on the performance and the radial force of the marine pump, the unsteady numerical simulation of the four different models is carried out. The radial forces on the impeller and the blades are obtained under different flow rate conditions. The time and frequency domain characteristics of radial resultant force on the impeller and the blades are analyzed and those of the impeller torque are researched. The results show that the radial forces of the impeller and the blades increase with the increase of the blade outlet angle at the same flow rate. With the same blade outlet angle, the radial forces decrease with the increase of the flow rate. The roundness of radial force vector diagram becomes more obvious with the decrease of the blade outlet angle. The root mean square (RMS) of radial force on the blades is about 30% of that on the impeller. The main frequency of radial force on the impeller and the blades is the axial passing frequency (APF), and that of impeller torque is the blade passing frequency (BPF), and there are peaks at the blade frequency multiplier. At the same flow rate, the main frequency and maximum fluctuation amplitudes on the impeller and the blades increase with the increase of the blade outlet angle. Meanwhile, the impeller torque increases with the increase of the blade outlet angle. With the same blade outlet angle, the main frequency, maximum fluctuation amplitudes, and the impeller torque decrease with the increase of the flow rate. The amplitude difference decreases with the increase of the flow rate. The blade outlet angle has an obvious greater influence on the radial forces and fluctuation at the small flow rate. The vibration test shows that the vibration intensities of model 25 and model 35 are less than 2.5 mm/s, and the vibration intensity of model 25 is about 0.2 mm/s less than that of model 35.